Electrical stimulation as a treatment intervention to improve function, edema or pain following acute lateral ankle sprains: A systematic review. Issue 4 (November 2015) - Feger, Mark A.; Goetschius, John; Love, Hailey; Saliba, Sue A.; Hertel, Jay
Abstract: The purpose of this systematic review was to assess whether electrical stimulation (ES), when used in conjunction with a standard treatment, can reduce levels of functional impairment, edema, and pain compared to a standard treatment alone, in patients following a lateral ankle sprain. We searched PubMed, CINAHL, SportDiscus, and Medline (OVID) databases through June 2014 using the terms " ankle sprain or ankle sprains or ligament injury or ligamentous injury, " and "electric stimulation or electric stimulation or electrotherapy ." Our search identified four randomized control trials, of which, neuromuscular ES and high-voltage pulsed stimulation were the only two ES modalities utilized. Effect sizes and 95% confidence intervals (CI) were estimated using Cohen's d for comparison between treatment groups. Three of four effect sizes for function had 95% CI that crossed zero. Twenty-four of the thirty-two effect sizes for edema had 95% CI that crossed zero. All effect sizes for pain had 95% CI that crossed zero. Therefore, the use of ES is not recommended as a means to improve function, reduce edema, or decrease pain in the treatment of acute lateral ankle sprains. Highlights: Electrical stimulation is used to enhance recovery following lateral ankle sprains. We review the clinical evidence in regards to this use of electrical stimulation. Outcomes assessed in our review include edema, pain, and function. Electrical stimulation does not improve outcomes following lateral ankle sprain.